Identificación genética de especies de leismania en zonas endémicas en la Región Sur del Ecuador - Ochoa Romero, Janeth Alexandra (2019)
Leishmaniasis is a disease caused by protozoan species Leishmania, it is transmitted by the bite of the infected fly belonging to the genus Lutzomyia. The causal agent presents a flagellum in the insect for what is called a promastigote, and it lacks this when parasitizing the macrophages of vertebrate hosts for what is called amastigote. Leishmaniasis has domestic and wild reservoirs such as dogs, foxes, rodents, wolves. In Ecuador, lesions caused by L. braziliensis, L. panamensis, L. guyanensis, L. mexicana, and L. amazonensis have been identified. Its epidemiology depends on the characteristics of the parasite species, ecological and local characteristics of the places where it is transmitted, previous and current exposure of the human population. In the present study, an active search for suspected cases, sampling and identification of circulating leishmania species in the cantons of Centinela del Cóndor and Nangaritza in the province of Zamora Chinchipe was proposed. The sample consisted of people with presumptive symptoms for leishmaniasis of 100 families surveyed in those cantons. Samples were taken for microscopy scraping and lymphatic aspirate for culture of three people who presented a lesion in left lower limb, face and left lower limb respectively, in the form of an ulcer with irregular and painless edges, in order to identify Leishmania, spp; to identify the species, a fragment of the gene encoding the HSP70 heat shock protein was amplified, L. braziliensis was identified, making alignments in the MEGA program and, comparing with available species in GenBank, using the obtained sequences, the phylogenetic tree was elaborated , the results were socialized to students and teachers of the career of Clinical Laboratory. KEY WORDS: leishmaniasis, PCR, identification, hsp70, Zamora.